Bag‐of‐binary‐features for fast image representation. Issue 7 (1st April 2015) - Lee, Suwon; Choi, SuGil; Yang, Hyun S.
Abstract : The possibility of integrating binary features into the bag‐of‐features (BoFs) model is explored. The set of binary features extracted from an image are packed into a single vector form, to yield the bag‐of‐binary‐features (BoBFs). The efficient BoBF feature extraction and quantisation provide fast image representation. The trade‐off between accuracy and efficiency in BoBF compared with BoF is investigated through image retrieval tasks. Experimental results demonstrate that BoBF is a competitive alternative to BoF when the run‐time efficiency is critical.